A macro stress testing framework for assessing systemic risks in the banking sector - Jérôme Henry; Christoffer Kok (European Central Bank (ECB), 2013)
The use of macro stress tests to assess bank solvency has developed rapidly over the past few years. This development was reinforced by the financial crisis, which resulted in substantial losses for banks and created general uncertainty about the banking sector's loss-bearing capacity. Macro stress testing has proved a useful instrument to help identify potential vulnerabilities within the banking sector and to gauge its resilience to adverse developments. To support its contribution to safeguarding financial stability and its financial sector-related work in the context of EU/IMF Financial Assistance Programmes, and looking ahead to the establishment of the Single Supervisory Mechanism (SSM), the ECB has developed a top-down macro stress testing framework that is used regularly for forward-looking bank solvency assessments. This paper comprehensively presents the main features of this framework and illustrates how it can be employed for various policy analysis purposes.
Keywords: C32; E60; H62; 330; banking sector; financial crisis; macro stress test; macro-prudential policy; Systemic risk; Finanzkrise; Bankenliquidität; Systemrisiko; Bankenaufsicht; Finanzmarktaufsicht; EU-Staaten